Influence of hydrogen and carbon monoxide on reduction behavior of iron oxide at high temperature: Effect on reduction gas concentrations - Abu Tahari M.N.; Salleh F.; Tengku Saharuddin T.S.; Samsuri A.; Samidin S.; Yarmo M.A. (Elsevier Ltd, 2024)
Indexed by Scopus/ERA